2015
DOI: 10.1149/06801.1499ecst
|View full text |Cite
|
Sign up to set email alerts
|

Screen Printed Porous La0.20Sr0.25Ca0.45TiO3 Fuel Electrode Scaffold Microstructures: Optimisation of Interaction with Impregnated Catalysts for More Durable Performance

Abstract: La0.20Sr0.25Ca0.45TiO3 (LSCTA-) shows promise as a novel Solid Oxide Fuel Cell anode backbone material (to replace Ni-based cermets). Thick film ceramic processing techniques have been used as the primary method in controlling the characteristics of the fuel electrode (layer thickness, porosity, grain connectivity and the ultimate interaction with catalyst particles) in order to produce a microstructural architecture which has the potential to deliver higher electronic (and ionic) conductivity, improved curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…These initial results suggested that the 8YSZ and 6ScSZ powders may show a higher sinteractivity, including a better ability to densify, than the 6Sc1CeSZ powder and would most likely require higher loadings of dispersant to form a homogeneous tape casting slurry. Considering the LSCTAanode-support powders, the TLSCTA-appeared to be very coarse, with a monomodal distribution and a d50 value of 1.74 µm (as also shown in previous research into ESC) (23,24). However, the bimodal distributions of the milled TLSCTA-and PLSCTA-powders gave rise to d50 values of 0.505 µm and 0.323 µm, respectively.…”
Section: Physical and Thermal Characterisation Of Raw Materialssupporting
confidence: 77%
“…These initial results suggested that the 8YSZ and 6ScSZ powders may show a higher sinteractivity, including a better ability to densify, than the 6Sc1CeSZ powder and would most likely require higher loadings of dispersant to form a homogeneous tape casting slurry. Considering the LSCTAanode-support powders, the TLSCTA-appeared to be very coarse, with a monomodal distribution and a d50 value of 1.74 µm (as also shown in previous research into ESC) (23,24). However, the bimodal distributions of the milled TLSCTA-and PLSCTA-powders gave rise to d50 values of 0.505 µm and 0.323 µm, respectively.…”
Section: Physical and Thermal Characterisation Of Raw Materialssupporting
confidence: 77%
“…However, despite the sufficient number of scientific research studies in this direction and the large amount of known literature data in the field of photocatalytic decomposition, interest to this direction has not stopped. In the last few years, much attention has been paid to studying the possibilities and prospects in the direction of increasing not only the efficiency of photocatalytic reactions, but also increasing their resistance to external influences and corrosion processes [21][22][23][24][25]. In this regard, one of the avenues in this direction of research is the method of doping titanates with rare-earth elements, which allows not only increasing of their resistance to external influences, but also changing their electronic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above, the main purpose of this study is to investigate the effect of doping CaTiO 3 ceramics with lanthanum at different concentrations to increase not only photocatalytic activity, but also to study the influence of the phase composition of ceramics on the optical and strength properties. Doping with lanthanum is caused by the possibility of increasing not only the resistance of perovskite-like ceramics to corrosion and mechanical damage, but also increasing photo-catalytic activity [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[ 67 ] The ink was also found to possess low‐level thixotropic behavior (time‐dependent shear‐thinning), which is useful in removing mesh marks left behind by the screen‐printing process, without loss of overall electrode geometry due to the relaxation of the ink. [ 64,65,68 ] Therefore, the authors reported that this ink was considered to be most optimal to carry forward for screen‐printing trials using screens of differing mesh count (per inch). In brief, screen printing of this 75 wt% LSCT A− loading ink onto 8YSZ substrates with a 230 mesh count screen yielded microstructures with a more advantageous combination of high porosity and grain connectivity than those printed with a 325 mesh count screen, after sintering under the same conditions.…”
Section: Introductionmentioning
confidence: 99%